(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The study focuses on the case of Vincent Lambert, a patient in a vegetative state for which the Grand Chamber (European Court of Human Rights), has confirmed the decision of the French Council of State to withdraw artificial nutrition because this represents an unreasonable obstinacy. However, following a second consultation with the doctors, it was considered appropriate to continue the nutrition, showing that the previous decision is questionable and that the precautionary principle would be more appropriate in bioethical issues. Through the analysis of several documents, the author shows the importance of distinguishing between euthanasia and assisted suicide on the one hand, and therapeutic abstention on the other. The author agrees with dissenting opinion from the Grand Chamber judges and considers that the interruption of the nutrition to patients in a vegetative state is a form of euthanasia and this is in contrast with the directions of Council of Europe and Italian Constitutional principles. Deprivation of food and water, indeed, with the effect of causing the death, based on poor prognosis, is incompatible with the principle of equality and with the principle of recognition of the inalienable rights to every man.